Primary Mathematics School Teachers’ Technological, Pedagogical and Content Knowledge and Learners’ Achievement - Patalinghug, Janiene T.; Arnado, Alvic A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The goal of this study is to determine the level of primary mathematics school teacher’s Technological Pedagogical and Content Knowledge (TPACK) and the achievement of learners of the selected districts of the Division of Butuan City, Agusan del Norte. The participating teachers were able to complete the survey on the following components namely, technology knowledge, content knowledge, pedagogical knowledge, pedagogical content knowledge, technological pedagogical knowledge, technology and pedagogy and content knowledge, and the mathematics achievement level of learners. This study employed descriptive – correlational design to describe the variables and the relationship among them. The results revealed that teachers have high knowledge on the seven components of TPACK and obtained highest average on the technological pedagogical knowledge directly proportional with the mathematics achievement level of the learners. Though teachers showcasing their mastery level of teaching, still they need the support of technology to address the immediate concerns in dealing with the new normal. Thus, teachers may be encouraged to attend conferences, seminar – workshops, and training related to technology specifically training on technology applications that promotes easy techniques in solving word problems in primary grade mathematics.